Ytterbium‐Enriched Outmost Shell for Enhanced Upconversion Single Molecule Imaging and Interfacial Triplet Energy Transfer. Issue 6 (14th January 2022) - Hu, Jialing; Guan, Daoming; Zhao, Bingjie; Zhang, Yanxin; Qiu, Xiaochen; Zhang, Yunxiang; Liu, Qian
Abstract: Lanthanide‐based upconversion single molecule imaging (u‐SMI) is of great interest due to its excellent photostability and background‐free detection. However, the dim brightness strongly hampers its application in quantitative studies. An inert shell can effectively enhance the upconversion brightness, especially for highly doped upconversion nanocrystals in which surface quenching is the dominant nonirradiative pathway. Here, it is discovered that inert shell is actually a drawback for u‐SMI in a volume‐constrained system and sensitizer Yb 3+ doped outmost shell outperforms inert shell in single molecule imaging condition, which indicates that the number of Yb 3+ sensitizers is the fundamental bottleneck for u‐SMI and the surface quenching can be noncritical. The effect of Yb 3+ ‐enriched shell on the interfacial energy transfer‐based dye‐sensitized upconversion is also investigated and orders of magnitude enhancement is obtained over the previously reported design. Abstract : One of the challenges in upconversion nanomaterials is the dim brightness. Herein, the surface‐related energy loss and photon capture capability are balanced to optimize single particle brightness in a volume‐constrained nanoparticle. It is found that ytterbium‐enriched outmost shell can effectively enhance the upconversion luminescence at single molecule imaging condition.